2013
DOI: 10.1179/1476830513y.0000000061
|View full text |Cite
|
Sign up to set email alerts
|

Impaired IQ and academic skills in adults who experienced moderate to severe infantile malnutrition: A 40-year study

Abstract: Objectives To evaluate IQ and academic skills in adults who experienced an episode of moderate to severe infantile malnutrition and a healthy control group, all followed since childhood in the Barbados Nutrition Study. Methods IQ and academic skills were assessed in 77 previously malnourished adults (mean age=38.4 years; 53% male) and 59 controls (mean age=38.1 years; 54% male). Group comparisons were carried out by multiple regression and logistic regression, adjusted for childhood socioeconomic factors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 25 publications
1
62
0
1
Order By: Relevance
“…Malnutrition in the first year of life causes long-term impairments in cognition and, independent of the lower IQ, attention deficits (primarily inattention), lasting into adulthood(2, 23). Given the strong link between childhood malnutrition and adult attention-deficit hyperactivity disorder (ADHD)(23), together with the cognitive deficits and lower IQ(2), we then asked whether such neuropsychiatric sequels are associated with specific DNA methylation signatures.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Malnutrition in the first year of life causes long-term impairments in cognition and, independent of the lower IQ, attention deficits (primarily inattention), lasting into adulthood(2, 23). Given the strong link between childhood malnutrition and adult attention-deficit hyperactivity disorder (ADHD)(23), together with the cognitive deficits and lower IQ(2), we then asked whether such neuropsychiatric sequels are associated with specific DNA methylation signatures.…”
Section: Resultsmentioning
confidence: 99%
“…The research design and sample recruitment for the Barbados Nutrition Study have been described elsewhere(2, 4, 10). Epigenetic data were collected in the original cohort and their offspring between 2012 and 2014, when the G1 participants were in their fifth decade of life and their offspring were young adults (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, although group differences in IQ in the Barbados sample are relatively stable over time (Waber, et al, 2013), the observed profiles are not necessarily direct sequelae of brain alterations associated with the episode of malnutrition. They may also reflect the developmental interactions of the neurologically compromised child with the physical and social environment, and in particular with an impoverished environment (Gottlieb & Halpern, 2002; Wachs, 2009).…”
Section: Discussionmentioning
confidence: 99%